COMPARISON OF MOTOR SKILLS OF YOUNG SCHOOL STUDENTS - Aleksandar Pajkić; Radenko Dobraš; Duško Lepir (Sport Scientific And Practical Aspects, 2025)
The aim of this paper was to investigate whether in the younger school-age there is a decline in motor skills compared to previous generations. The study was conducted on a sample of students of the fourth and fifth grades of elementary schools, tested in two different periods (234 students tested in 2011 and 2012 and 311 students tested in 2017 and 2018). The student's motor skills were tested and the EUROFIT test battery was applied. Differences in motor skills were determined by Mann-Whitney (U test) test. Analyzing the obtained results, it was found that there are statistically significant differences in five of the seven tests, which show that a newer generation of students has achieved significantly lower results than the older generation in both sexes. Although there has not been a long period of time between these two tests, it can be assumed that in the past few years there have been marked changes in the way of life of children, which resulted in reduced physical activity and poor motor skills